The Effect of Export Tax on Indonesia Palm Oil Derivative Products - Muhammad Rizza Gani; I Made Krisna Yudhana Wisnu Gupta (Universitas Negeri Semarang, 2024)
In international trade, oilseed products are one of the most highly traded agricultural products (others include grains and meat), making this trade one of crucial importance for many countries, either through production or utilization (Krugman,2009). Based on that, since 2008 the government has issued a policy of imposing taxes on palm oil and its derivatives with the aim of ensuring domestic availability and to encourage the growth of the national industry. This study examines the impact of the imposition of export tax policies on the export performance of palm oil and its derivatives. We use panel data on exports of palm oil products and their derivatives to 10 main export destination countries during 2008 – 2021 period using Poisson Pseudo Maximum Likelihood (PPML) estimation method. The estimation results show that export taxes imposed on palm oil derivative products had a significant negative impact, while high export tax policy on the upstream sector (input) for palm oil effectively encouraged an increase in palm oil derivative exports through the availability of cheap palm oil as input for the palm oil industry.